1999
DOI: 10.2337/diacare.22.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Standardized comparison of glucose intolerance in west African-origin populations of rural and urban Cameroon, Jamaica, and Caribbean migrants to Britain.

Abstract: The transition in glucose intolerance from Cameroon to Jamaica and Britain suggests that environment determines diabetes prevalence in these populations of similar genetic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 5 publications
5
99
3
Order By: Relevance
“…The high prevalence of diabetes (16%) in this study reflects trends in sub‐Saharan Africa, where urban residence is associated with a 2‐ to 5‐fold higher risk of impaired glucose tolerance 58, 59. Oza‐Frank and Narayan60 reported that, compared with other immigrants in the United States, African men ranked second (7.8%) in prevalence of diabetes, and African women ranked third (4.6%).…”
Section: Discussionmentioning
confidence: 58%
“…The high prevalence of diabetes (16%) in this study reflects trends in sub‐Saharan Africa, where urban residence is associated with a 2‐ to 5‐fold higher risk of impaired glucose tolerance 58, 59. Oza‐Frank and Narayan60 reported that, compared with other immigrants in the United States, African men ranked second (7.8%) in prevalence of diabetes, and African women ranked third (4.6%).…”
Section: Discussionmentioning
confidence: 58%
“…High prevalence of obesity in women surpassed the levels reported in other developing countries in Latin America (Martorell et al, 2000) and Africa (Martorell et al, 2000;Mokhtar et al, 2001). Of interest, in our international study (Mbanya et al, 1999;Cruickshank et al, 2001), 35% of Afro-Caribbean women in Britain were obese, as were 37% of women in Pomerleau et al's (1999) study. The alarming level of obesity among women is of public health significance and a challenge to scarce resources.…”
Section: Discussionmentioning
confidence: 66%
“…Fieldworker procedures were rigorously standardised, a process repeated within teams every month, with regular cross-site visits every 4 months. Standardised measures of anthropometry such as BMI and WHR were taken by trained fieldworkers, after subjects had responded to a detailed lifestyle questionnaire [1].…”
Section: Baseline Examinationmentioning
confidence: 99%
“…Differences in disease rates between migrant and nonmigrant populations may supply important clues to the aetiology and hence the mechanism of disease [1]. For any ethnic group, lifestyle has a profound effect on insulin metabolism and on the incidence of type 2 diabetes and cardiovascular disease [2].…”
Section: Introductionmentioning
confidence: 99%